2015
DOI: 10.1007/s10397-015-0891-7
|View full text |Cite
|
Sign up to set email alerts
|

SOS save our surgeons: Stress levels reduced by robotic surgery

Abstract: Robotic-assisted laparoscopic surgery (RALS) is making an increasingly significant contribution to the field of gynaecological surgery. RALS offers similar patient benefits to standard laparoscopic surgery (SLS) with a potentially more ergonomically friendly and less stressful environment for the surgeon. However, our understanding of how RALS may potentially reduce physiological stress on the surgeon is currently limited. To assess how performing surgical tasks using RALS in comparison to SLS impacts on hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…In a nutshell, this study showed that RASC was associated with lower neck, shoulder, and back discomfort scores [ 35 ]. Stress levels, measured by skin conductance level, and heart rate were significantly lower in surgically inexperienced medical students performing tasks with the robot when compared to laparoscopic instrumentation [ 37 ]. These findings will need to be validated in a proper RCT and a more homogenous population of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In a nutshell, this study showed that RASC was associated with lower neck, shoulder, and back discomfort scores [ 35 ]. Stress levels, measured by skin conductance level, and heart rate were significantly lower in surgically inexperienced medical students performing tasks with the robot when compared to laparoscopic instrumentation [ 37 ]. These findings will need to be validated in a proper RCT and a more homogenous population of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The normalized GSR average value was found to be the most relevant parameter in terms of its relationship with stress, with an increase of 261% between the baseline and stressful phases of the experiment and a high, significantly positive correlation with the subjective stress rating that was stated by the participants. The relevance of the GSR average values has already been demonstrated in the literature and appears as one of the trending parameters for measuring stress in surgical environments [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most popular approaches are mainly descriptive (i.e., the mean, standard deviation and sum of the GSR signal). For instance, Hurley et al [ 62 ] used these metrics to find the differences in the stress levels between standard laparoscopic surgery and robotic surgery. These metrics have also been used to validate their relation with other variables, specifically with workload [ 63 ] and performance [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…This self‐tolerance for suboptimal centred view in RALS might be consequent to full ownership of the surgical procedure by the robotic surgeon, with no need for coordination with the assistant. This also could explain the lower surgeon stress during RALS compared to CLS 17 . However, it is not possible to estimate retrospectively to what degree a well‐centred view was achieved based on verbal and manual corrections from the surgeon during CLS.…”
Section: Discussionmentioning
confidence: 99%